ENGLISH TEACHER PROFESSIONAL DEVELOPMENT IN INDONESIA: THE CHALLENGES AND OPPORTUNITIES - Anchieta Ave Avillanova; Paulus Kuswandono (English Review: Journal of English Education, 2019)
This study investigates the challenges and opportunities of junior high school English teacher professional development in Indonesia. The objectives of the study are to examine the English teachers’ challenges and needs to develop their TPD. This qualitative study employed questionnaire and in-depth interview as the main instruments for data collection. The findings revealed that the challenges of TPD related to, firstly, program timing as the program was carried out during working hours; and, secondly, lack of information about workshop schedule from the government (Education Office) because, geographically, some schools are located in remote areas. The study also explored the teachers’ needs for TPD concerning student assessment, classroom management, knowledge and understanding of English, content of performance standards, giving instruction, ICT skills for teaching, teaching students with special learning needs, and school management and administration. Suggestion for further study concerns with the bottom-up approach of carrying TPD based on the teachers’ real needs as opposed to given programs.